HUBUNGAN LITERASI KEUANGAN DENGAN PERUBAHAN KESEJAHTERAAN MASYARAKAT PASCA PEMBERIAN GANTI KERUGIAN TANAH UNTUK PEMBANGUNAN JALAN TOL DI DESA BONGASWETAN, KABUPATEN MAJALENGKA - Anshori, Alfian Najib; Asjhari, Ahsan (Jurnal Sosial Ekonomi Pekerjaan Umum, 2015)
Land acquisition on road project often experienced with rejection caused by community disagreement towards value of land compensation. Land acquisition could emerge community concerns about how they live in the future. It is closely related to society’s perception of the government has given compensation loss couldn’t fulfill their live needs in the future. Government used assumption that compensation could increase affected communities welfare. This article aimed to determine the change of community welfare who received land compensations. This article also aimed to determine the relationship between changes in community welfare with financial literacy. This article used land acquisition case in Bongas Wetan village, Majalengka as part of road construction Cikampek-Palimanan (Cipali). Data obtained using questionaire. Scoring analysis used to determine the change of community welfare, while the relationship between variables described by Spearman’s rho correlation. Most of them have change in, either increase (32%) or decrease (46%) and no relationship between financial literacy and community welfare. There are need for further research about determined the financial literacy indicators and other factors that could influenced communtity welfare after compensation payment.